Gold(I)‐Catalyzed N‐Desulfonylative Amination versus N‐to‐O 1, 5‐Sulfonyl Migration: A Versatile Approach to 1‐Azabicycloalkanes. Issue 31 (16th June 2016) - Miaskiewicz, Solène; Gaillard, Boris; Kern, Nicolas; Weibel, Jean‐Marc; Pale, Patrick; Blanc, Aurélien
Abstract: Valuable 1‐azabicycloalkane derivatives have been synthesized through a novel gold(I)‐catalyzed desulfonylative cyclization strategy. An ammoniumation reaction of ynones substituted at the 1‐position with an N ‐sulfonyl azacycle took place in the presence of a gold cation by intramolecular cyclization of the disubstituted sulfonamide moiety onto the triple bond. Depending on the size of the heterocyclic ring and substitution of the substrates, two unprecedented forms of nucleophilic attack on the sulfonyl group were exploited, that is, a N‐desulfonylation in the presence of an external protic O nucleophile (37–87 %, 10 examples) and a unique N‐to‐O 1, 5‐sulfonyl migration (60–98 %, 9 examples). Abstract : Worth their weight in gold : The great value of sulfonamides in gold catalysis is highlighted by two hydroamination reactions that occur by migration or cleavage of sulfonyl group (see scheme). These unprecedented gold‐promoted sulfonyl‐transfer reactions open the way to appealing synthetic applications of these robust nitrogen‐protecting groups, as demonstrated by the formation of versatile azabicycles.